PELATIHAN MENYUSUN DAN MENGENDALIKAN ANGGARAN KEUANGAN RUMAH TANGGA DI KAMPUNG PANGABASEN DESA GAPURA TIMUR - Enza Enza Resdiana; Irma Irawati Puspaningrum (Dharma: Jurnal Pengabdian Masyarakat, 2022)
Basic skills in managing family finances need to be owned by every family, especially housewives. The low level of public education results in bad habits in managing family expenses. Therefore, to break the chain of low poverty, it can also be done by providing training on the importance of management and periodic counseling to the community regarding training and education in family financial management, which is expected to be able to open minds and attract people's interest to change life-saving behavior. The method of implementing this community service activity is through training carried out involving the Pangabasen Hamlet community who are members of a group of women who receive conditional cash assistance from the Ministry of Social Affairs of the Republic of Indonesia and interactive communication. The results of the training activities for compiling and controlling household financial budgets and the use of social assistance provided by the government to families had a positive response during the training, this group of women was very enthusiastic about the training provided so that the training carried out ran optimally. only given training this time but at other times also want community service with other topics that educate.